Neuron Specific Enolase Levels’ Relationship with CT Scan Images on Head Injury Patients - Imanharibsar, Hary Romeo (Indonesian Journal of Multidisciplinary Science, 2023)
Head injuries can cause closed injuries, or open injuries that can penetrate the skin, starting from the skin as the outermost layer, to the bones of the skull, blood vessels of the brain, and brain tissue as cranio-cerebral injuries. The authors wanted to prove whether there is a picture between NSE serum levels and a CT scan of the head that describes the severity of a head injury. The type of research used in this research is analytic observational research. The study design in this study was a cross sectional which aims to describe the levels of Neuron Specific Enolase (NSE) serum with CT scan images of head injured patients at RSUP Dr. M. Djamil City of Padang. This research was conducted in the Emergency Room of RSUP Dr. M. Djamil, Padang City as the sampling location and the Biomedical Laboratory of the Faculty of Medicine, Andalas University as the research location and the research time starts from February to June 2023. Head injury patients who underwent head CT scans at the M.Djamil Hospital Padang Emergency Room were found with the following characteristics: age 20-29 years, male sex, CT scan of the head in the form of MLS<5mm/cistern narrowing, increased NSE level, severity mild head injury (GCS 13-15).